Pekarangan Pinggir Kota untuk Menyangga Ekosistem Perkotaan: Pemanfaatan dan Keanekaragaman Tanaman - Siti Nurul Rofiqo Irwan; Valentina Dwi Suci Handayani; Haviah Havidhotul Ilmiah (Institut Pertanian Bogor, 2023)
Home garden “pekarangan” plays an important role in conserving plant diversity in urban and suburban area. The suburban area including of pekarangan is a buffer area to preserve the quality of the urban environment. This study aimed to determine the utilization and plant diversity in suburban pekarangan of Yogyakarta. This research was carried out in Maguwoharjo using a survey method for 105 samples of home garden. Data were collected by observation using purposive sampling based on size of yard area. The results showed that the utilization of pekarangan in Maguwoharjo was dominated by ornamental plants, consist of sri rejeki (Aglaonema sp., Araceae), orchids (Dendrobium, Orchidaceae) and frangipani trees (Plumeria sp., Apocynaceae). Other functions of home garden were fruit plant and ground cover/grass. There was found 90 species of plants from 49 families, 27 species of trees, 60 species of shrubs, and three species of ground cover. The Shannon Wienner plant diversity index (H') was above 3 indicating the high category and the Evenness species evenness index (E) was close to 1 indicating a stable ecosystem condition. The H’ and E index based on size of yard area showed 3.74 and 0.88 (very small, <20 m2), 3.90 and 0,.89 (small, 20–50 m2), 3.44 and 0.88 (medium, 50–100 m2), 3.52 and 0.93 (big, 100–200 m2), 3.06 and 0.94 (very big, >200 m2). The results showed that suburban home garden “pekarangan” can support quality of urban ecosystem and its preservation. Keywords: evenness index, Maguwoharjo Sleman, shannon wienner index, suburban pekarangan, Yogyakarta